2007
DOI: 10.1152/ajpheart.00198.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reverse electron flow-induced ROS production is attenuated by activation of mitochondrial Ca2+-sensitive K+ channels

Abstract: Heinen A, Aldakkak M, Stowe DF, Rhodes SS, Riess ML, Varadarajan SG, Camara AK. Reverse electron flow-induced ROS production is attenuated by activation of mitochondrial Ca 2ϩ -sensitive K ϩ channels. Am J Physiol Heart Circ Physiol 293: H1400-H1407, 2007. First published May 18, 2007; doi:10.1152/ajpheart.00198.2007.-Mitochondria generate reactive oxygen species (ROS) dependent on substrate conditions, O2 concentration, redox state, and activity of the mitochondrial complexes. It is well known that the FADH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 42 publications
(65 reference statements)
7
85
0
Order By: Relevance
“…It is suggested that mitochondrial K ϩ channels, often identified as effectors of protection by preconditioning, could be these mediators (10,27,32,34). However, their role in this mechanism is questionable since their activation has been correlated with both increase and decrease in ROS production (20,49). These controversial findings may result from differential behavior of these channels depending on the metabolic state of the cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that mitochondrial K ϩ channels, often identified as effectors of protection by preconditioning, could be these mediators (10,27,32,34). However, their role in this mechanism is questionable since their activation has been correlated with both increase and decrease in ROS production (20,49). These controversial findings may result from differential behavior of these channels depending on the metabolic state of the cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…Following IR injury Heinen et al demonstrated more efficient forward electron flow with NS1619 treatment. 44 In addition, multiple groups have documented increased respiration following BKCa activation using NS1619 and NS11021. 41, 46 However, in endothelial cells, iberiotoxinsensitive NS1619-induced respiration was associated with increased non-phosphorylating respiration or proton leak.…”
Section: Structure/functionmentioning
confidence: 99%
“…40 NS1619 was also shown to attenuate ROS production in isolated mitochondria under conditions to stimulate reverse electron flow. 44 The overall consensus is that activation of the BKCa channel limits ROS following IR, and that this may be one of the major cardioprotective benefits of channel activation.…”
Section: Mechanism Of Mitochondrial Bkca-channel-mediated Cardioprotementioning
confidence: 99%
“…The figure was created by adapting information from (176,195,255), respectively. generation from the cardiac mitochondria, the synthesis of H 2 O 2 from the isolated mitochondria from hearts, or mitochondria in intact cardiac cells, can be determined in a fluorescence-based assay (106). Within these fluorescence-based assays, inhibition of the mitochondrial respiratory chain at any stage causes generation of large amounts of ROS (Fig.…”
Section: Figmentioning
confidence: 99%